Genetic Profile of Follicle Stimulating Hormone Receptor (rFSH) in Madrasin Crossbreed Cattle - Hidayah, Aisyah Shaumanur Artha; Utomo, Budi; Mustofa, Imam (Universitas Airlangga, 2021)
The aim of this study was to know about genetic profile of Folicle Stimulating Hormone Receptor (rFSH) in Madrasin crossbreed between Madura breed and Limousin breed (Madrasin). The research are using whole blood samples from Madura breed, Limousin breed, and Madrasin crossbreed. Madura breed and Madrasin crossbreed sample were taken from Galis, Pamekasan, East Java and Limousin breed is taken from Balai Embrio Ternak (BET) Cipelang, Bogor, West Java. Samples were used for genetic profile analysis such as DNA amplification with Polymerase Chain Reaction (PCR) method and DNA sequencing in Institute of Tropical Disease, Universitas Airlangga. The result showed that DNA fragment of rFSH is 211bp. In conclusion, this study can detect rFSH gene Madrasin crossbreed which is polymorpism.